The Bone Tree - Iles, Greg.; Petkoff, Robert; Ostrowka, Katie; Harper Audio (Firm) ([New York] : HarperAudio, 2015)
Penn Cage's father, Dr. Tom Cage, stands accused of murder and each effort to defend him unearths new, shocking secrets. At issue is the murder of Tom's former nurse, Viola Turner. The district attorney is quick to point the finger at Tom, citing his decades-old relationship with Viola. When Tom is taken into custody, Penn must explore the dangerous territory of Tom and Viola's shared history, set squarely in the most harrowing years of civil-rights-era Mississippi.
Keywords: Cage, Penn (Fictitious character) -- Fiction; Audiobooks; Natchez (Miss.) -- Fiction; Audiobooks; Suspense fiction; Mystery fiction